2010
DOI: 10.1590/s0102-05362010000300019
|View full text |Cite
|
Sign up to set email alerts
|

Características agronômicas de cultivares de alho em Diamantina

Abstract: Um estudo foi realizado, durante o período da safra 2007, com objetivo de avaliar as características agronômicas período de emergência das plântulas, altura de plantas, diâmetro de bulbos frescos e curados, números de bulbilhos por bulbo e produtividade comercial de quatorze cultivares de alho em Diamantina-MG. O delineamento experimental adotado foi de blocos casualizados, com quatro repetições, cujos tratamentos foram as cultivares de alho Gigante do Núcleo, Gigante de Lavínia, Gigante Roxo, Gigante Roxão, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 8 publications
3
9
0
8
Order By: Relevance
“…These results are similar to those found by Oliveira et al (2010) Regarding the titratable acidity depending on vernalization periods, cultivars and planting locations, the highest average acidity was found for the cultivar Gigante-do-Nucleo in Barauna when the bulb-seeds were vernalized for 10 days, and in Governador Dix-sept Rosado when vernalizated for 10, 20 and 30 DV. The cultivar BRS-Hozan had the highest average acidity with 20 DV in Barauna, and in the treatments without vernalization and with 20 and 30 DV in Governador Dix-sept Rosado, the last two being similar to 10 DV (Table 3).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…These results are similar to those found by Oliveira et al (2010) Regarding the titratable acidity depending on vernalization periods, cultivars and planting locations, the highest average acidity was found for the cultivar Gigante-do-Nucleo in Barauna when the bulb-seeds were vernalized for 10 days, and in Governador Dix-sept Rosado when vernalizated for 10, 20 and 30 DV. The cultivar BRS-Hozan had the highest average acidity with 20 DV in Barauna, and in the treatments without vernalization and with 20 and 30 DV in Governador Dix-sept Rosado, the last two being similar to 10 DV (Table 3).…”
Section: Resultssupporting
confidence: 89%
“…On the other hand, the national product supply in the domestic market has shown a gradual increase in recent years, thanks to the development of new technologies and cultivars in producing areas (OLIVEIRA et al, 2010;GUTIERREZ;ROCHA, 2014).…”
Section: Introdutionmentioning
confidence: 99%
“…The planting locations presented no statistically significant differences in plant height ( Figure 1B). Similar result was observed by Oliveira et al (2010), who found greater height for the BRS-Hozan compared to the Gigante-do-Nucleo, confirmed at 60, 90 and 120 DAP. Honorato (2012) also found the same results at 40, 60 and 120 DAP.…”
Section: Resultssupporting
confidence: 88%
“…Lower average bulb weight results were found by Honorato et al (2013), without bulb-seed vernalization, with bulbs with 9.14 g (Gigante-do-Nucleo) and 9.11 g (BRS-Hozan). Oliveira et al (2010) found different values in Diamantina, MG, with average bulb weight of 15.61 g (Gigante-do-Nucleo) and 12.61 g (BRS-Hozan), values that were lower than those found in the Western Mesoregion of Rio Grande do Norte State, Brazil.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation